Milk quality of dual-purpose cows supplemented with biological fish silage (Pterygoplichthys sp.) as a protein source - Castillo-Mercado, Raquel A.; Bucio-Galindo, Adolfo; Salinas-Hernández, Rosa M.; Aranda-Ibáñez, Emilio M.; Izquierdo-Reyes, Francisco; Ramos-Juárez, Jesús A. (Revista Colombiana de Ciencias Pecuarias, 2020)
Background: Devilfish (Pterygoplichthys sp.) is a pest of high impact in aquaculture production systems. Through a biological fermentation process, it could be used as a source of protein for dairy cows. However, milk palatability and smell could be limiting factors. Objective: to evaluate the quality of milk from cows supplemented with biological fish silage (Pterygoplichthys sp.) as a protein source. Methods: The treatments (T) evaluated were T1, 0% biological fish silage; T2, 10% biological fish silage; and T3, 20% biological fish silage. Twelve randomly selected cows were used in a Latin square experimental design, in which three treatments were tested with all of the cows during three time periods. Each period lasted 20 days (15-day adaptation period and 5-day experimental phase). Milk was analyzed for physicochemical, microbiological, sanitary condition and sensory characteristics. Analyses of variance were performed for all the response variables. Results: No significant differences for physicochemical variables were found among the treatments studied. Differences were observed in microbiological and sanitary variables among treatments, but values were in the range for high quality milk standards (˂100,000 CFU mL-1 aerobic mesophilic bacteria, and ˂400,000 somatic cells mL-1). In the sensory analyses, panelists did not detect strange odors nor fishy taste or odor in the milk of any of the treatments. Conclusion: Biological fish silage can be included up to 20% as a protein source in supplements for lactating cows.